2021
DOI: 10.3390/nano11061405
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Cycling Stability of Fe2WO6 Pseudocapacitive Electrode Materials

Abstract: The stability upon cycling of Fe2WO6 used as a negative electrode material for electrochemical capacitors was investigated. The material was synthesized using low temperature conditions for the first time (220 °C). The electrochemical study of Fe2WO6 in a 5 M LiNO3 aqueous electrolyte led to a specific and volumetric capacitance of 38 F g−1 and 240 F cm−3 when cycled at 2 mV·s−1, respectively, associated with a minor capacitance loss after 10,000 cycles. In order to investigate this very good cycling stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…The Rietveld refinement in the Pbcn space group, including a minor contribution (below 0.5%) from hematite (H peaks), is shown in Figure together with the cell parameters and crystallographic parameters; a crystallographic information file is provided in the Supporting Information. A Rietveld refinement based on laboratory X-ray data, very recently reported for a sample prepared by a polyol solution route, is in good agreement with this structural model . However, the excellent signal-to-noise ratio offered by our synchrotron data reveals that a few very small peaks remain unindexed at d = 5.60, 4.59, and 3.28 Å.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The Rietveld refinement in the Pbcn space group, including a minor contribution (below 0.5%) from hematite (H peaks), is shown in Figure together with the cell parameters and crystallographic parameters; a crystallographic information file is provided in the Supporting Information. A Rietveld refinement based on laboratory X-ray data, very recently reported for a sample prepared by a polyol solution route, is in good agreement with this structural model . However, the excellent signal-to-noise ratio offered by our synchrotron data reveals that a few very small peaks remain unindexed at d = 5.60, 4.59, and 3.28 Å.…”
Section: Resultssupporting
confidence: 87%
“…Historically, the interest in the properties of Fe 2 WO 6 was mostly focused on the magnetism and/or transport properties of its polymorphs, considered in the framework of the AB 2 O 6 structures combining a magnetic cation B with an A cation of high formal charge. In recent years, the environmentally benign character of iron has spurred the interest for iron-based oxides. Accordingly, Fe 2 WO 6 has become the focus of much more varied investigations regarding the photoelectrochemical activity, photocatalytic properties, reversible capacity as a lithium-ion battery electrode, , pseudocapacitance in electrochemical capacitors, magnetodielectric properties, thermoelectric properties, , and biological activity . Indeed, half of the ∼30 papers about Fe 2 WO 6 have been published since 2014, with 9 of them published since 2020.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It showed interesting pseudocapacitive performance in terms of volumetric capacitance thanks to the high density of this oxide and long-term cycling behavior was achieved with such electrode. 14 For this latter purpose, Fe 2 WO 6 sample was prepared using a polyol-mediated route at low temperature (220°C). A temperature-dependent X-ray diffraction study indicated, at 800°C, the formation of a well-crystallized phase whose diffraction peaks were successfully indexed into the cell of the α-PbO 2 structure (a α-PbO2 , b α-PbO2 , c α-PbO2 , Pbcn space group).…”
Section: Introductionmentioning
confidence: 99%